Analysing some issues with SOX. (1st January 2013) - Sy, Aida
The Sarbanes-Oxley Act legislation (the SOX) was triggered by a series of market failures that were exemplified by the bankruptcy of Enron, whose accounting errors inflated earning by almost $600 million since 1994. With assets of $62 billion, Enron was the largest bankruptcy case in US history. The Enron collapse was dwarfed several months later by the massive fraud and bankruptcy filing of WorldCom in July 2002, with $100 billion in assets. The changes in internal control required by SOX's executive arm – the Public Company Accounting Oversight Board (PCAOB) – imposed costs, that have given rise to appeals to rollback or repeal the requirements (for small firms, overseas firms, etc). One emerging technology – analytic monitoring – offers a possible answer to this impasse. It tenders a family of solutions that are potentially cheaper and more effective than traditional systems of control.